2019
DOI: 10.1002/cpns.68
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol‐Induced Preclinical Tardive Dyskinesia Model in Rats

Abstract: Haloperidol is a first‐generation antipsychotic used in the treatment of psychoses, especially schizophrenia. This drug acts by blocking dopamine D2 receptors, reducing psychotic symptoms. Notwithstanding its benefits, haloperidol also produces undesirable impacts, in particular extrapyramidal effects such as tardive dyskinesia (TD), which limit the use of this and related drugs. TD is characterized by repetitive involuntary movements occurring after chronic exposure therapy with haloperidol. Symptoms most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…However, it is important to acknowledge that there are numerous concerns and debates surrounding the use of animal models for studying TD. Our findings regarding OD induced by HP align with those of other researchers and our own previous studies [3][4][5][6][7][10][11][12]. In our experiments, rats treated with HP for 21 consecutive days exhibited a significant increase in the frequency of VCM and TP, along with impairments in oxidative defense and mitochondrial function.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, it is important to acknowledge that there are numerous concerns and debates surrounding the use of animal models for studying TD. Our findings regarding OD induced by HP align with those of other researchers and our own previous studies [3][4][5][6][7][10][11][12]. In our experiments, rats treated with HP for 21 consecutive days exhibited a significant increase in the frequency of VCM and TP, along with impairments in oxidative defense and mitochondrial function.…”
Section: Discussionsupporting
confidence: 92%
“…Not only do the characteristic features of HP-induced OD bear a strong resemblance to the symptoms of TD, but HP has also been implicated in the development of TD in humans. In rats, HP-induced changes in VCM (vacuous chewing movements) and TP (tongue protrusions) have proven to be a valuable model and an essential tool for identifying potential therapeutic agents for TD [3,4]. However, it is important to acknowledge that there are numerous concerns and debates surrounding the use of animal models for studying TD.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Senousy et al 2022 [17] identified that the BCG vaccine inhibited the PI3k/Akt/mTOR signaling pathway and was involved in the improvement of mitochondrial function and restored the antioxidant levels in the 3-NPA-treated rat brain, which shows the neuroprotective potential of the BCG vaccine. Similarly, in our previous study, BCG reduced oxidative stress markers and improved locomotor activity in QA-induced HD rats [37]. Our study findings also indicate that the BCG vaccine has an antioxidant property, as it restored antioxidants (GSH, SOD, and catalase) and lowered oxido-nitrosative stress markers (MDA and nitrite) in the rat striatum, providing neuroprotection from oxidative stress generated by haloperidol.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, researchers have developed a haloperidol-induced rodent model that provides similar symptomatic conditions to TD [37].…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned PK characteristics are undoubtedly helpful for obtaining good PD results in vivo . VMAT2 inhibitors can inhibit the release of dopamine and reduce rat locomotor activity, which is used as a substitute index to evaluate the efficacy of VMAT2 inhibitors ( Grigoriadis et al, 2017 ; Guzen et al, 2019 ; Li et al, 2019 ). The multi-target activity screen of SpectrumScreen ® Panel (Eurofins screen) demonstrated that (+)-13e had no effects on dopamine receptors, serotonin receptors, adrenergic receptors, dopamine transporter, norepinephrine transporter, five serotonin transporter, and so on.…”
Section: Discussionmentioning
confidence: 99%